Gambaran Darah Ikan Nila (Oreochromis niloticus) di Kolam Budidaya di Kecamatan Marpoyan Damai Kota Pekanbaru - Riauwaty, Morina; Syawal, Henni (Fakultas Perikanan dan Kelautan Universitas Riau, 2016)
The aim of the research is to describe the blood of Tilapia that had been cultured in a fishpond since June to December 2015. The ponds were located in Marpoyan Subdistrict, Pekanbaru city. Twenty samples were collected as much as 20 fish that consisted of 10 male and 10 female with the size ranging from 9.5 – 18.2 cm. The blood of the fish was taken with syringe via caudal vena as much of 1 ml. The blood parameters then were calculated in term of the number of hematocrit, leucocyte, erythrocyte, and leukocyte. The results showed that the amount of hematocrit and leukokrit were ranged between 10 – 31 % and 1.78 – 3.10 % consecutively. The total cell of erythrocyte ranged between 1,170,000 – 2,190,000 cell/mm3, and the total of leukosit were about 81,000 – 105,000 cell/mm3. In addition, the types of leukocyte found at this study were hepatocyte (53- 86%), thrombocyte (25 – 39%), monocyte and neutrophil between 1 – 3 %.